PERBANDINGAN PENGUNGKAPAN LAPORAN KEBERLANJUTAN INDUSTRI PERKERETAAPIAN DI INDONESIA BERDASARKAN GRI STANDAR 2021 - Nyimas Hafizah Astriliya; Annisa Nabila Hasan (E-Jurnal Akuntansi TSM, 2025)
The growing awareness of sustainability has led to increased corporate transparency and accountability, particularly through sustainability reporting. This study aims to analyze the disclosure of sustainability issues in three Indonesian railway companies, PT MRT Jakarta, PT LRT Jakarta, and PT Kereta Commuter Indonesia, based on the GRI 2021 Standards. Using a descriptive qualitative approach, the study examines sustainability reports and related documents. The findings reveal that material issues in the railway industry are closely linked to public service functions as well as environmental and social impacts. Economic and social disclosures are generally more extensive than environmental ones, with notable variations among companies. The ownership structure, operational age, and corporate status all influence the extent and form of sustainability reporting. This study underscores the need to enhance the quality of sustainability disclosures and promote the adoption of more consistent standards to strengthen transparency and accountability in the public transportation sector.